A cerebello-thalamo-cortical pathway transmits reward-based post-error signals for motor timing correction during learning in male mice - Rie Ako; Shin-Ichiro Terada; Masanori Matsuzaki (Nature Communications)
Abstract The cerebellum is critical for motor timing control and error-driven motor learning. To reveal how the cerebellum transmits these process-relevant signals to the premotor cortex, we conducted two-photon calcium imaging of cerebellar-thalamocortical axons in the premotor cortex in male mice during a self-timing lever-pull task that required 1–1.7 s of waiting after cue onset. In non-expert sessions with many lever-pulls being made before the 1-s waiting, the axons of thalamic neurons that received cerebellar outputs exhibited larger transient activity immediately after the cue onset in post-error (i.e., post-non-rewarded) trials than in post-success trials, and the waiting time and success rate were greater in post-error trials than in post-success trials. In expert sessions, the post-error-specific activity or behavior was absent. Instead, ramping activity toward lever-pull onset that did not depend on the waiting time shortened in expert sessions in comparison with non-expert sessions. Our results suggest that the cerebellum emits the reward-based post-error signal for waiting time adjustment during learning, and the well-tuned motor timing signal after learning.